Pemberdayaan Anak Jalanan Melalui Rumah Singgah: Empowering Street Children Through Transitional Shelters - Sarwan Sarwan (Fenomena, 2002)
The 1997 economic crisis exacerbated the vulnerability of street children in Indonesia, leading to their disempowerment in accessing education and economic opportunities. This qualitative study used a phenomenological approach and a case study design to describe the profile of street children, patterns of educational and economic empowerment, their responses to a drop-in center, and the constraints faced by Yayasan Paramitra in Malang City. Data were collected through participatory observation, in-depth interviews, and document analysis, then analyzed using data reduction, display, and conclusion drawing. Key findings reveal that most street children come from poor families, work on the streets due to economic pressures, and face threats from security officers and thugs. Empowerment was implemented through community-based, street-based, and center-based approaches, yet it was constrained by children’s lack of seriousness, inadequate shelter facilities, and the absence of sustainable work partnerships. In conclusion, the drop-in center model is participatively effective but requires cross-sectoral support. Recommendations include allocating social funds, actively engaging parents and communities, and developing standardized participatory guidelines for program sustainability. Krisis ekonomi 1997 memperparah kerentanan anak jalanan di Indonesia, menciptakan ketidakberdayaan dalam akses pendidikan dan ekonomi. Penelitian kualitatif dengan pendekatan fenomenologi dan strategi studi kasus ini bertujuan mendeskripsikan profil anak jalanan, pola pemberdayaan pendidikan dan ekonomi, respons mereka terhadap rumah singgah, serta kendala yang dihadapi Yayasan Paramitra di Kota Malang. Data dikumpulkan melalui observasi partisipatif, wawancara mendalam, dan studi dokumentasi, lalu dianalisis dengan reduksi data, penyajian data, dan penarikan kesimpulan. Temuan utama menunjukkan bahwa anak jalanan umumnya berasal dari keluarga miskin, bekerja di jalanan karena tekanan ekonomi, serta menghadapi ancaman dari aparat keamanan dan preman. Pemberdayaan dilakukan melalui pendekatan berbasis masyarakat, jalanan, dan panti, namun terkendala oleh ketidakseriusan anak, kurangnya fasilitas rumah singgah, dan belum adanya mitra kerja berkelanjutan. Kesimpulannya, model rumah singgah efektif secara partisipatif tetapi membutuhkan dukungan lintas sektor. Rekomendasi mencakup perlunya alokasi dana sosial, pelibatan aktif orang tua dan masyarakat, serta penyusunan pedoman baku partisipatoris untuk keberlanjutan program.